ANALISIS MOTIVASI KERJA UNTUK MENINGKATKAN KINERJA PEGAWAI BADAN PENGAWAS OBAT DAN MAKANAN - Pratiwi, Nurhayati; Zulkifli; Derriawan; Agustinus (SEKOLAH PASCASARJANA PRESS, 2021)
This study aims to analyze the placement system and workload on work motivation and analyze the effect of the placement and workload system on performance in the National of Drug and Food Control. The number of respondents used amounted to 310 people. Collecting data using the method of observation, questionnaires and interviews. In this study, the method used in this study is a positivistic quantitative method. While the data used in quantitative methods and to test hypotheses using SEM (Structural Equation Modeling) statistical methods using Lisrel software and qualitative hypothesis testing will be analyzed using EFE, IFE, TOWS matrix and QSPM. The results of the study analyze that employee placement affects work motivation, workload affects work motivation, work environment affects work motivation, employee placement affects employee performance, workload affects employee performance, work environment affects employee performance, work motivation affects performance employee